BUKHARA AS A CENTER OF SCIENCE AND EDUCATION IN THE MUSLIM EAST - Roxat Mamadshoyeva (Modern American Journals, 2025)
This article analyzes the traditional education system historically developed in the city of Bukhara, focusing on its social, religious, and cultural foundations based on historical sources. It discusses the structure, educational process, and teaching methods of maktabxonas and madrasas that operated in Bukhara during the 9th–12th centuries, as well as the environment in which prominent scholars were educated. The article also examines the descriptions provided by enlightened figures such as Fitrat and Aini, highlighting both the strengths and shortcomings of educational institutions of that time. The topic holds significant historical and cultural value.
Keywords: Bukhara, traditional education, maktabkhona, madrasa, Fitrat, Aini, historical source, scientific heritage, educational process.